Pendampingan pada Anak Usia Dini dalam Menciptakan Lingkungan Belajar yang Menyenangkan (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Early Childhood Education (ECE) is a developmental effort aimed at children from birth to six years old, a period known as the golden age of child development. The success of the learning process at this stage greatly depends on the quality of assistance provided by the adults around the child. This community service activity aimed to assist early childhood children in creating a fun learning environment through a collage-making activity. The activity involved 10 young children at Kober Peupado Malanuza on April 20, 2026, for one lesson hour, facilitated by students of the PG-PAUD Study Program, STKIP Citra Bakti, through preparation, implementation, and evaluation stages. The assistance was carried out through a play-based learning approach, positive communication, and the provision of engaging media. The results show that the children were enthusiastic, willing to try, and confident in presenting their work, creating a safe and enjoyable learning atmosphere, with no children refusing to participate in the activity. Thus, appropriate assistance through play activities becomes an important foundation in optimizing early childhood growth and development, and parents and teachers are recommended to actively contribute to creating a fun learning environment for children.